mathlib documentation

number_theory.zsqrtd.basic

ℤ[√d] #

The ring of integers adjoined with a square root of d : ℤ.

After defining the norm, we show that it is a linearly ordered commutative ring, as well as an integral domain.

We provide the universal property, that ring homomorphisms ℤ√d →+* R correspond to choices of square roots of d in R.

structure zsqrtd (d : ) :
Type

The ring of integers adjoined with a square root of d. These have the form a + b √d where a b : ℤ. The components are called re and im by analogy to the negative d case.

@[instance]
Equations
theorem zsqrtd.ext {d : } {z w : ℤ√d} :
z = w z.re = w.re z.im = w.im
def zsqrtd.of_int {d : } (n : ) :

Convert an integer to a ℤ√d

Equations
theorem zsqrtd.of_int_re {d : } (n : ) :
theorem zsqrtd.of_int_im {d : } (n : ) :
def zsqrtd.zero {d : } :

The zero of the ring

Equations
@[instance]
Equations
@[simp]
theorem zsqrtd.zero_re {d : } :
0.re = 0
@[simp]
theorem zsqrtd.zero_im {d : } :
0.im = 0
@[instance]
Equations
def zsqrtd.one {d : } :

The one of the ring

Equations
@[instance]
def zsqrtd.has_one {d : } :
Equations
@[simp]
theorem zsqrtd.one_re {d : } :
1.re = 1
@[simp]
theorem zsqrtd.one_im {d : } :
1.im = 0
def zsqrtd.sqrtd {d : } :

The representative of √d in the ring

Equations
@[simp]
theorem zsqrtd.sqrtd_re {d : } :
@[simp]
theorem zsqrtd.sqrtd_im {d : } :
def zsqrtd.add {d : } :
ℤ√d → ℤ√d → ℤ√d

Addition of elements of ℤ√d

Equations
@[instance]
def zsqrtd.has_add {d : } :
Equations
@[simp]
theorem zsqrtd.add_def {d : } (x y x' y' : ) :
{re := x, im := y} + {re := x', im := y'} = {re := x + x', im := y + y'}
@[simp]
theorem zsqrtd.add_re {d : } (z w : ℤ√d) :
(z + w).re = z.re + w.re
@[simp]
theorem zsqrtd.add_im {d : } (z w : ℤ√d) :
(z + w).im = z.im + w.im
@[simp]
theorem zsqrtd.bit0_re {d : } (z : ℤ√d) :
(bit0 z).re = bit0 z.re
@[simp]
theorem zsqrtd.bit0_im {d : } (z : ℤ√d) :
(bit0 z).im = bit0 z.im
@[simp]
theorem zsqrtd.bit1_re {d : } (z : ℤ√d) :
(bit1 z).re = bit1 z.re
@[simp]
theorem zsqrtd.bit1_im {d : } (z : ℤ√d) :
(bit1 z).im = bit0 z.im
def zsqrtd.neg {d : } :

Negation in ℤ√d

Equations
@[instance]
def zsqrtd.has_neg {d : } :
Equations
@[simp]
theorem zsqrtd.neg_re {d : } (z : ℤ√d) :
(-z).re = -z.re
@[simp]
theorem zsqrtd.neg_im {d : } (z : ℤ√d) :
(-z).im = -z.im
def zsqrtd.mul {d : } :
ℤ√d → ℤ√d → ℤ√d

Multiplication in ℤ√d

Equations
@[instance]
def zsqrtd.has_mul {d : } :
Equations
@[simp]
theorem zsqrtd.mul_re {d : } (z w : ℤ√d) :
(z * w).re = (z.re) * w.re + (d * z.im) * w.im
@[simp]
theorem zsqrtd.mul_im {d : } (z w : ℤ√d) :
(z * w).im = (z.re) * w.im + (z.im) * w.re
@[instance]
def zsqrtd.monoid {d : } :
Equations
@[instance]
Equations
@[instance]
def zsqrtd.ring {d : } :
Equations
@[instance]
def zsqrtd.distrib {d : } :
Equations
def zsqrtd.conj {d : } :

Conjugation in ℤ√d. The conjugate of a + b √d is a - b √d.

Equations
@[simp]
theorem zsqrtd.conj_re {d : } (z : ℤ√d) :
z.conj.re = z.re
@[simp]
theorem zsqrtd.conj_im {d : } (z : ℤ√d) :
z.conj.im = -z.im
@[simp]
theorem zsqrtd.conj_zero {d : } :
0.conj = 0
@[simp]
theorem zsqrtd.conj_one {d : } :
1.conj = 1
@[simp]
theorem zsqrtd.conj_neg {d : } (x : ℤ√d) :
(-x).conj = -x.conj
@[simp]
theorem zsqrtd.conj_add {d : } (x y : ℤ√d) :
(x + y).conj = x.conj + y.conj
@[simp]
theorem zsqrtd.conj_sub {d : } (x y : ℤ√d) :
(x - y).conj = x.conj - y.conj
@[simp]
theorem zsqrtd.conj_conj {d : } (x : ℤ√d) :
x.conj.conj = x
@[instance]
@[simp]
theorem zsqrtd.coe_nat_re {d : } (n : ) :
@[simp]
theorem zsqrtd.coe_nat_im {d : } (n : ) :
n.im = 0
theorem zsqrtd.coe_nat_val {d : } (n : ) :
n = {re := n, im := 0}
@[simp]
theorem zsqrtd.coe_int_re {d : } (n : ) :
n.re = n
@[simp]
theorem zsqrtd.coe_int_im {d : } (n : ) :
n.im = 0
theorem zsqrtd.coe_int_val {d : } (n : ) :
n = {re := n, im := 0}
@[instance]
@[simp]
theorem zsqrtd.of_int_eq_coe {d : } (n : ) :
@[simp]
theorem zsqrtd.smul_val {d : } (n x y : ) :
(n) * {re := x, im := y} = {re := n * x, im := n * y}
@[simp]
theorem zsqrtd.muld_val {d : } (x y : ) :
zsqrtd.sqrtd * {re := x, im := y} = {re := d * y, im := x}
@[simp]
@[simp]
theorem zsqrtd.smuld_val {d : } (n x y : ) :
(zsqrtd.sqrtd * n) * {re := x, im := y} = {re := (d * n) * y, im := n * x}
theorem zsqrtd.decompose {d x y : } :
{re := x, im := y} = x + zsqrtd.sqrtd * y
theorem zsqrtd.mul_conj {d x y : } :
{re := x, im := y} * {re := x, im := y}.conj = (x) * x - ((d) * y) * y
theorem zsqrtd.conj_mul {d : } {a b : ℤ√d} :
(a * b).conj = (a.conj) * b.conj
theorem zsqrtd.coe_int_add {d : } (m n : ) :
(m + n) = m + n
theorem zsqrtd.coe_int_sub {d : } (m n : ) :
(m - n) = m - n
theorem zsqrtd.coe_int_mul {d : } (m n : ) :
m * n = (m) * n
theorem zsqrtd.coe_int_inj {d m n : } (h : m = n) :
m = n
theorem zsqrtd.coe_int_dvd_iff {d : } (z : ) (a : ℤ√d) :
z a z a.re z a.im
def zsqrtd.sq_le (a c b d : ) :
Prop

Read sq_le a c b d as a √c ≤ b √d

Equations
theorem zsqrtd.sq_le_of_le {c d x y z w : } (xz : z x) (yw : y w) (xy : zsqrtd.sq_le x c y d) :
zsqrtd.sq_le z c w d
theorem zsqrtd.sq_le_add_mixed {c d x y z w : } (xy : zsqrtd.sq_le x c y d) (zw : zsqrtd.sq_le z c w d) :
c * x * z d * y * w
theorem zsqrtd.sq_le_add {c d x y z w : } (xy : zsqrtd.sq_le x c y d) (zw : zsqrtd.sq_le z c w d) :
zsqrtd.sq_le (x + z) c (y + w) d
theorem zsqrtd.sq_le_cancel {c d x y z w : } (zw : zsqrtd.sq_le y d x c) (h : zsqrtd.sq_le (x + z) c (y + w) d) :
zsqrtd.sq_le z c w d
theorem zsqrtd.sq_le_smul {c d x y : } (n : ) (xy : zsqrtd.sq_le x c y d) :
zsqrtd.sq_le (n * x) c (n * y) d
theorem zsqrtd.sq_le_mul {d x y z w : } :
(zsqrtd.sq_le x 1 y dzsqrtd.sq_le z 1 w dzsqrtd.sq_le (x * w + y * z) d (x * z + (d * y) * w) 1) (zsqrtd.sq_le x 1 y dzsqrtd.sq_le w d z 1zsqrtd.sq_le (x * z + (d * y) * w) 1 (x * w + y * z) d) (zsqrtd.sq_le y d x 1zsqrtd.sq_le z 1 w dzsqrtd.sq_le (x * z + (d * y) * w) 1 (x * w + y * z) d) (zsqrtd.sq_le y d x 1zsqrtd.sq_le w d z 1zsqrtd.sq_le (x * w + y * z) d (x * z + (d * y) * w) 1)
def zsqrtd.nonnegg (c d : ) :
→ Prop

"Generalized" nonneg. nonnegg c d x y means a √c + b √d ≥ 0; we are interested in the case c = 1 but this is more symmetric

Equations
theorem zsqrtd.nonnegg_comm {c d : } {x y : } :
theorem zsqrtd.nonnegg_neg_pos {c d a b : } :
theorem zsqrtd.nonnegg_pos_neg {c d a b : } :
theorem zsqrtd.nonnegg_cases_right {c d a : } {b : } :
(∀ (x : ), b = -xzsqrtd.sq_le x c a d)zsqrtd.nonnegg c d a b
theorem zsqrtd.nonnegg_cases_left {c d b : } {a : } (h : ∀ (x : ), a = -xzsqrtd.sq_le x d b c) :
def zsqrtd.norm {d : } (n : ℤ√d) :
Equations
theorem zsqrtd.norm_def {d : } (n : ℤ√d) :
n.norm = (n.re) * n.re - (d * n.im) * n.im
@[simp]
theorem zsqrtd.norm_zero {d : } :
0.norm = 0
@[simp]
theorem zsqrtd.norm_one {d : } :
1.norm = 1
@[simp]
theorem zsqrtd.norm_int_cast {d : } (n : ) :
n.norm = n * n
@[simp]
theorem zsqrtd.norm_nat_cast {d : } (n : ) :
n.norm = (n) * n
@[simp]
theorem zsqrtd.norm_mul {d : } (n m : ℤ√d) :
(n * m).norm = (n.norm) * m.norm
theorem zsqrtd.norm_eq_mul_conj {d : } (n : ℤ√d) :
(n.norm) = n * n.conj
@[simp]
theorem zsqrtd.norm_neg {d : } (x : ℤ√d) :
(-x).norm = x.norm
@[simp]
theorem zsqrtd.norm_conj {d : } (x : ℤ√d) :
theorem zsqrtd.norm_nonneg {d : } (hd : d 0) (n : ℤ√d) :
0 n.norm
theorem zsqrtd.norm_eq_one_iff {d : } {x : ℤ√d} :
theorem zsqrtd.norm_eq_one_iff' {d : } (hd : d 0) (z : ℤ√d) :
theorem zsqrtd.norm_eq_zero_iff {d : } (hd : d < 0) (z : ℤ√d) :
z.norm = 0 z = 0
theorem zsqrtd.norm_eq_of_associated {d : } (hd : d 0) {x y : ℤ√d} (h : associated x y) :
x.norm = y.norm
def zsqrtd.nonneg {d : } :
ℤ√d → Prop

Nonnegativity of an element of ℤ√d.

Equations
def zsqrtd.le {d : } (a b : ℤ√d) :
Prop
Equations
@[instance]
def zsqrtd.has_le {d : } :
Equations
def zsqrtd.lt {d : } (a b : ℤ√d) :
Prop
Equations
@[instance]
def zsqrtd.has_lt {d : } :
Equations
@[instance]
def zsqrtd.decidable_nonnegg (c d : ) (a b : ) :
Equations
@[instance]
Equations
@[instance]
def zsqrtd.decidable_le {d : } (a b : ℤ√d) :
Equations
theorem zsqrtd.nonneg_cases {d : } {a : ℤ√d} :
a.nonneg(∃ (x y : ), a = {re := x, im := y} a = {re := x, im := -y} a = {re := -x, im := y})
theorem zsqrtd.nonneg_add_lem {d x y z w : } (xy : {re := x, im := -y}.nonneg) (zw : {re := -z, im := w}.nonneg) :
({re := x, im := -y} + {re := -z, im := w}).nonneg
theorem zsqrtd.nonneg_add {d : } {a b : ℤ√d} (ha : a.nonneg) (hb : b.nonneg) :
(a + b).nonneg
theorem zsqrtd.le_refl {d : } (a : ℤ√d) :
a a
theorem zsqrtd.le_trans {d : } {a b c : ℤ√d} (ab : a b) (bc : b c) :
a c
theorem zsqrtd.nonneg_iff_zero_le {d : } {a : ℤ√d} :
a.nonneg 0 a
theorem zsqrtd.le_of_le_le {d : } {x y z w : } (xz : x z) (yw : y w) :
{re := x, im := y} {re := z, im := w}
theorem zsqrtd.le_arch {d : } (a : ℤ√d) :
∃ (n : ), a n
theorem zsqrtd.nonneg_total {d : } (a : ℤ√d) :
theorem zsqrtd.le_total {d : } (a b : ℤ√d) :
a b b a
@[instance]
Equations
theorem zsqrtd.add_le_add_left {d : } (a b : ℤ√d) (ab : a b) (c : ℤ√d) :
c + a c + b
theorem zsqrtd.le_of_add_le_add_left {d : } (a b c : ℤ√d) (h : c + a c + b) :
a b
theorem zsqrtd.add_lt_add_left {d : } (a b : ℤ√d) (h : a < b) (c : ℤ√d) :
c + a < c + b
theorem zsqrtd.nonneg_smul {d : } {a : ℤ√d} {n : } (ha : a.nonneg) :
((n) * a).nonneg
theorem zsqrtd.nonneg_muld {d : } {a : ℤ√d} (ha : a.nonneg) :
theorem zsqrtd.nonneg_mul_lem {d x y : } {a : ℤ√d} (ha : a.nonneg) :
({re := x, im := y} * a).nonneg
theorem zsqrtd.nonneg_mul {d : } {a b : ℤ√d} (ha : a.nonneg) (hb : b.nonneg) :
(a * b).nonneg
theorem zsqrtd.mul_nonneg {d : } (a b : ℤ√d) :
0 a0 b0 a * b
theorem zsqrtd.not_sq_le_succ (c d y : ) (h : 0 < c) :
¬zsqrtd.sq_le (y + 1) c 0 d
@[class]
structure zsqrtd.nonsquare (x : ) :
Prop

A nonsquare is a natural number that is not equal to the square of an integer. This is implemented as a typeclass because it's a necessary condition for much of the Pell equation theory.

Instances
theorem zsqrtd.d_pos {d : } [dnsq : zsqrtd.nonsquare d] :
0 < d
theorem zsqrtd.divides_sq_eq_zero {d : } [dnsq : zsqrtd.nonsquare d] {x y : } (h : x * x = (d * y) * y) :
x = 0 y = 0
theorem zsqrtd.divides_sq_eq_zero_z {d : } [dnsq : zsqrtd.nonsquare d] {x y : } (h : x * x = ((d) * y) * y) :
x = 0 y = 0
theorem zsqrtd.not_divides_sq {d : } [dnsq : zsqrtd.nonsquare d] (x y : ) :
(x + 1) * (x + 1) (d * (y + 1)) * (y + 1)
theorem zsqrtd.nonneg_antisymm {d : } [dnsq : zsqrtd.nonsquare d] {a : ℤ√d} :
a.nonneg(-a).nonnega = 0
theorem zsqrtd.le_antisymm {d : } [dnsq : zsqrtd.nonsquare d] {a b : ℤ√d} (ab : a b) (ba : b a) :
a = b
theorem zsqrtd.eq_zero_or_eq_zero_of_mul_eq_zero {d : } [dnsq : zsqrtd.nonsquare d] {a b : ℤ√d} :
a * b = 0a = 0 b = 0
theorem zsqrtd.mul_pos {d : } [dnsq : zsqrtd.nonsquare d] (a b : ℤ√d) (a0 : 0 < a) (b0 : 0 < b) :
0 < a * b
theorem zsqrtd.norm_eq_zero {d : } (h_nonsquare : ∀ (n : ), d n * n) (a : ℤ√d) :
a.norm = 0 a = 0
@[ext]
theorem zsqrtd.hom_ext {R : Type} [comm_ring R] {d : } (f g : ℤ√d →+* R) (h : f zsqrtd.sqrtd = g zsqrtd.sqrtd) :
f = g
@[simp]
theorem zsqrtd.lift_symm_apply_coe {R : Type} [comm_ring R] {d : } (f : ℤ√d →+* R) :
@[simp]
theorem zsqrtd.lift_apply_apply {R : Type} [comm_ring R] {d : } (r : {r // r * r = d}) (a : ℤ√d) :
(zsqrtd.lift r) a = (a.re) + ((a.im)) * r
def zsqrtd.lift {R : Type} [comm_ring R] {d : } :
{r // r * r = d} (ℤ√d →+* R)

The unique ring_hom from ℤ√d to a ring R, constructed by replacing √d with the provided root. Conversely, this associates to every mapping ℤ√d →+* R a value of √d in R.

Equations
theorem zsqrtd.lift_injective {R : Type} [comm_ring R] [char_zero R] {d : } (r : {r // r * r = d}) (hd : ∀ (n : ), d n * n) :

lift r is injective if d is non-square, and R has characteristic zero (that is, the map from into R is injective).